2020
DOI: 10.3390/cells9061509
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory and Pain-Relieving Effects of AR170, an Adenosine A3 Receptor Agonist, in a Rat Model of Colitis

Abstract: The pharmacological activation of A3 receptors has shown potential usefulness in the management of bowel inflammation. However, the role of these receptors in the control of visceral hypersensitivity in the presence of intestinal inflammation has not been investigated. The effects of AR170, a potent and selective A3 receptor agonist, and dexamethasone (DEX) were tested in rats with 2,4-dinitrobenzene sulfonic acid (DNBS)-induced colitis to assess their tissue inflammatory parameters. The animals received AR170… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…AL170 mitigates the colonic damage and inflammation, reducing the release of TNF-α, IL-1β, and myeloperoxidase. AL170 was demonstrated to have an efficacy comparable to that of dexamethasone, one of the most used drugs in the colitis treatment and other inflammatory bowel diseases [ 131 ]. The activation of A 3 ARs resulted able to decrease the infiltration of inflammatory cells and the production of inflammatory mediators thus softening visceral pain [ 131 ].…”
Section: Ars and Painmentioning
confidence: 99%
See 1 more Smart Citation
“…AL170 mitigates the colonic damage and inflammation, reducing the release of TNF-α, IL-1β, and myeloperoxidase. AL170 was demonstrated to have an efficacy comparable to that of dexamethasone, one of the most used drugs in the colitis treatment and other inflammatory bowel diseases [ 131 ]. The activation of A 3 ARs resulted able to decrease the infiltration of inflammatory cells and the production of inflammatory mediators thus softening visceral pain [ 131 ].…”
Section: Ars and Painmentioning
confidence: 99%
“…AL170 was demonstrated to have an efficacy comparable to that of dexamethasone, one of the most used drugs in the colitis treatment and other inflammatory bowel diseases [ 131 ]. The activation of A 3 ARs resulted able to decrease the infiltration of inflammatory cells and the production of inflammatory mediators thus softening visceral pain [ 131 ]. A further study revealed that the treatment with A 3 AR agonists is useful in another model of abdominal pain induced by colitis.…”
Section: Ars and Painmentioning
confidence: 99%
“…Dexamethasone, widely known as an anti-in ammatory medication (23,24), is expedient to decline chemotherapy side effects as well as the neurological symptoms in patients with brain cancers (23). However, due to the suppressive properties of dexamethasone especially on the anti-tumor T-cell responses (25), identifying a competent alternative seems necessary.…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of the mechanism of escape by the tumor from the immune system is the TME [ 106 ], which is characterized by a hypoxic state and is rich in inhibitory ligands and cytokines, such as IL-10 and TGF-β, which lead to tolerance by the immune cells towards the tumor [ 107 , 108 ] ( Figure 3 ). These conditions determine the increase in the expression of CD39 and CD73 [ 89 ], present on the surface of the tumor by stimulating the production of extracellular adenosine, by activating A2AAR.…”
Section: The Role Of Adenosine In Glioblastoma Multiformementioning
confidence: 99%